2000
DOI: 10.1016/s0735-1097(99)00485-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimyosin autoantibodies are associated with deterioration of systolic and diastolic left ventricular function in patients with chronic myocarditis

Abstract: Antimyosin autoantibodies are associated with worse development of left ventricular systolic function and diastolic stiffness in patients with chronic myocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
90
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(101 citation statements)
references
References 41 publications
6
90
1
4
Order By: Relevance
“…It is interesting that in both our DQ8 NOD model and in many humans with IDCM (32,33), autoantibodies against cardiac myosin occur. We were able to show moderate T cell proliferative responses to this antigen as well.…”
Section: Discussionmentioning
confidence: 98%
“…It is interesting that in both our DQ8 NOD model and in many humans with IDCM (32,33), autoantibodies against cardiac myosin occur. We were able to show moderate T cell proliferative responses to this antigen as well.…”
Section: Discussionmentioning
confidence: 98%
“…Many patients show heart-specific autoantibodies (3,4), and immunosuppressive therapy can improve cardiac function in DCM patients who show no evidence of viral or bacterial genomes in heart biopsy samples (5). These observations suggest that autoimmunity plays an important role in myocarditis as well as contributing to the progression to cardiomyopathy and heart failure (6).…”
mentioning
confidence: 99%
“…Meanwhile, the first experimental observations were made by several investigators, suggesting a possible involvement of autoimmune mechanisms to cardiac autoantigens; in particular, a mouse model for myosin-induced autoimmune myocarditis was described by the Neu et al [5]. In addition, various groups in the late 80s and early 90s reported the presence of circulating anti-heart autoantibodies against myosin as well as other autoantigens in acute and chronic myocarditis or dilated cardiomyopathy, in keeping with the hypothesis of autoimmunity being involved in a subset of patients [6][7][8][9][10][11][12][13][14]. A retrospective multicenter registry from the USA coordinated by Cooper et al [15] reported the efficacy of immunosuppressive therapy in a rare but lethal form of myocarditis, e.g., giant cell myocarditis.…”
mentioning
confidence: 76%